Plano de Imanência e Univocidade do Ser em Deleuze - Jairo Dias Carvalho (DoisPontos, 2011)
The text intends to show that, despite of Deleuze's affirmation that the univocity has three great moments in the history of philosophy, Duns Scoto, Spinoza and Nietzsche, his philosophy constitutes a contemporary moment of this history. The idea of Plane of Immanence will be the personal Deleuze's answer to the problem of the opposition between the analogy of proportion and the univocity of being on the history of philosophy.